1978
DOI: 10.3109/00498257809061254
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fate of 1-Hexylcarbamoyl-5-fluorouracil in Rats

Abstract: 1. The metabolic fate of a new antitumour agent, 1-hexylcarbamoyl-5-fluoro [6-14C]uracil (14C-HCFU) in rats after oral administration was compared with that of 5-fluoro[6-14C]uracil (14C-FU). 2. Tissue radioactivity reached a max. 1 to 3 h after administration of 14C-HCFU and 0.5 h after 14C-FU. 3. Both drugs were excreted rapidly, mostly in urine. Expired 14CO2 from 14C-HCFU was significantly less than that from 14C-FU. 4. Unchanged FU was not detected in plasma 3 h after administration of 14C-FU, whereas FU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The anticancer properties of carmofur have been attributed to the ability of this agent to generate 5–FU1314242526, a pyrimidine analog that inhibits DNA synthesis in tumor cells by blocking thymidylate synthase27. Nevertheless, the lack of positive correlation between carmofur-induced inhibition of thymidylate synthetase activity and cell proliferation is suggestive of a more complex mechanism of action14.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer properties of carmofur have been attributed to the ability of this agent to generate 5–FU1314242526, a pyrimidine analog that inhibits DNA synthesis in tumor cells by blocking thymidylate synthase27. Nevertheless, the lack of positive correlation between carmofur-induced inhibition of thymidylate synthetase activity and cell proliferation is suggestive of a more complex mechanism of action14.…”
Section: Discussionmentioning
confidence: 99%
“…Carmofur was eluted by CH 3 CN/H 2 O (50/50, v/v, 0.25% phosphoric acid) with a flow rate of 1.0 ml min −1 at 40°C and determined by UV detection at 260 nm. Carmofur in the lung homogenate with concentrations ranging from 500 to 20,000 ng/ml was prepared for the external standard curve (Kobari et al, 1978).…”
Section: Methodsmentioning
confidence: 99%
“…However, a study using 14 C radioactive carmofur and 5‐FU demonstrated that carmofur was rapidly absorbed and reached highest tissue concentration within 1–3 h of oral administration, whereas it was only 0.5 h for 5‐FU in rats. Equimolar administration of the 14 C‐carmofur and 14 C‐5‐FU indicated that the pyrimidine ring in carmofur degrades slowly and therefore, unchanged 5‐FU was detected for a longer period of time (>5 h) for carmofur than it is for 14 C‐5‐FU (Kobari et al, 1978). Ooi et al (2001) studied the plasma level of 5‐FU after oral administration of carmofur in mice.…”
Section: Pharmacokinetics and Metabolites Of Carmofurmentioning
confidence: 99%
“…Carmofur has also been observed to cross the blood‐brain barrier and distribute itself in brain compartment which can be attributed to the lipophilic aliphatic tail of the compound, however, to what extent is not well understood (Iigo et al, 1979). About 90% of the drug was found to be excreted through urine within 48 h of administration, some into the air, and a very low amount in the feces (IIGO et al, 1981; Kobari et al, 1978). The peaks for carmofur were observed between 1 and 2 h in human and a half‐life of about 2 h. In addition, the peak concentration for the metabolite 5‐FU appeared at the same time (Ikehira et al, 1999).…”
Section: Pharmacokinetics and Metabolites Of Carmofurmentioning
confidence: 99%
See 1 more Smart Citation